Pembuatan Buku Panduan Media Promosi Perpustakaan di Perpustakaan Amanah Masjid Taqwa Muhammadiah Sumatera Barat - Rahmi, Auli; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
On this paper, discussed about the stages of writing Guidebook of Library Media Promotion in Amanah Library of Taqwa Muhammadiah Mosque Sumatera Barat. The purpose of this paper is to describe the process of making a Guidebook of Library Media Promotion in Amanah Library of Taqwa Muhammadiah Mosque Sumatera Barat. The method that is used a descriptive method, and the data collecting technique throught direct observation and interviews. The observation is applied by observasingÂ  how Amananah Library of Taqwa Muhammadiah Mosque Sumatera Barat to promoted the library. And then, by interviews, the writer giving by direct question to the staff of Amananah Library of Taqwa Muhammadiah Mosque Sumatera Barat about the promote the library. The steps of writing the Guidbook are: first, collecting data and information by interviewing technique. The interview is applayed with the staff of Amananah Library of Taqwa Muhammadiah Mosque Sumatera Barat about the promote the library. Second, before writing the guide book, the writer makes the draft of guide book. Third, making the guide book.Keyword: guide book, library, promotion.